1994
DOI: 10.3382/ps.0730288
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Requirement for Cholecalciferol in the Absence of Ultraviolet Light

Abstract: Studies were conducted to determine the basic requirement of the bird for cholecalciferol in the absence of ultraviolet light by utilizing filter sleeves on fluorescent lights in the room and brooder. In Experiment 1, some pens were fitted with filter tubes and some lights were turned off. All the birds received a cholecalciferol-deficient diet. Birds with ultraviolet light excluded grew slowly, developed rickets (95%), had low plasma calcium, and low bone ash (27%); whereas birds exposed to the fluorescent li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 3 publications
3
20
0
2
Order By: Relevance
“…The authors concluded that the vitamin D 3 requirements of broilers up to 14 d of age are much higher than earlier estimates and may be related to the higher calcium requirements of the modern broiler genotypes. The results of the present study are also in agreement with the conclusions obtained by other investigators who, using diets with unbalanced Ca: P levels to induce TD, observed a reduction in the leg disorders when using, in particular, the active metabolite 1,25-dihydroxyvitamin D 3 (Rennie et al, 1993;Edwards Jr. et al, 1994, 2000Fritts & Waldroup, 2003). It is likely that, when TD is induced by hypocalcaemia or vitamin-deficient diets, this condition may be secondary to rickets, which might be mitigated by correcting calcium homeostasis.…”
Section: Use Of Vitamin D To Reduce Lameness In Broilers Reared In Hasupporting
confidence: 82%
See 2 more Smart Citations
“…The authors concluded that the vitamin D 3 requirements of broilers up to 14 d of age are much higher than earlier estimates and may be related to the higher calcium requirements of the modern broiler genotypes. The results of the present study are also in agreement with the conclusions obtained by other investigators who, using diets with unbalanced Ca: P levels to induce TD, observed a reduction in the leg disorders when using, in particular, the active metabolite 1,25-dihydroxyvitamin D 3 (Rennie et al, 1993;Edwards Jr. et al, 1994, 2000Fritts & Waldroup, 2003). It is likely that, when TD is induced by hypocalcaemia or vitamin-deficient diets, this condition may be secondary to rickets, which might be mitigated by correcting calcium homeostasis.…”
Section: Use Of Vitamin D To Reduce Lameness In Broilers Reared In Hasupporting
confidence: 82%
“…Broilers had access to natural lighting and indirect UV light, as it is the case of most broiler houses in Brazil, which may have enhanced the vitamin D status. Several authors (Edwards Jr. et al, 1994;Edwards Jr., 2003) established the optimal doses and methods of secure use of UV light to chicks to increase their vitamin D status under laboratory conditions. This may provide an alternative to supplying high levels of vitamin D in the starter diets.…”
Section: Use Of Vitamin D To Reduce Lameness In Broilers Reared In Hamentioning
confidence: 99%
See 1 more Smart Citation
“…Edwards et al (1994) and Elliot and Edwards (1997), however, concluded that at least 20 m g D3/kg was required from 1 to 16 d of age when exposure of chicks to uorescent lighting was prevented. The chicks in our studies were con ned to batteries containing no lighting, but overhead uorescent lights were present on a continuous 24 h basis.…”
Section: Discussionmentioning
confidence: 94%
“…As exigências para máximo desempenho normalmente são menores que 25 μg/kg ração (Edwards et al, 1994;NRC, 1994). A fase inicial, período em que ocorre alta taxa de crescimento do tecido esquelético, além da imaturidade do trato digestório (digestão e absorção de lipídios e compostos lipossolúveis), é provavelmente mais sensível ao aumento na suplementação.…”
Section: Resultsunclassified